2023
DOI: 10.3389/fmats.2023.1225481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical grinding on the physicochemical properties of silica aerogels

Rutian Li,
Shuisheng Zeng,
Kai Shen
et al.

Abstract: Mechanical grinding is a facile method to get silica aerogels (SAs) with various particle sizes. However, the relationship between the grinding parameters and physicochemical properties is still unclear. In this study, we concentrated on the effects of grinding time and grinding speed on the physical and chemical properties of silica aerogels. The results reveal that the physicochemical properties of silica aerogels are more sensitive to the grinding speed rather than the grinding time. When the grinding speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The water-adsorption capacities of the broken and unbroken silica gels after the fifth run were tested separately. The results shown in Figure f reveal that the water-adsorption capacities of the fresh and unbroken silica gels were comparable (0.32 g/g), whereas it decreased to 0.25 g/g for the broken gel because of the collapse of the internal pore structure and reduction in the specific surface area . Therefore, the decrease in the product yield in the successive reactions was ascribed to the breaking of the dewatering reagent.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The water-adsorption capacities of the broken and unbroken silica gels after the fifth run were tested separately. The results shown in Figure f reveal that the water-adsorption capacities of the fresh and unbroken silica gels were comparable (0.32 g/g), whereas it decreased to 0.25 g/g for the broken gel because of the collapse of the internal pore structure and reduction in the specific surface area . Therefore, the decrease in the product yield in the successive reactions was ascribed to the breaking of the dewatering reagent.…”
Section: Resultsmentioning
confidence: 93%
“…The results shown in Figure 5f reveal that the wateradsorption capacities of the fresh and unbroken silica gels were comparable (0.32 g/g), whereas it decreased to 0.25 g/g for the broken gel because of the collapse of the internal pore structure and reduction in the specific surface area. 47 Therefore, the decrease in the product yield in the successive reactions was ascribed to the breaking of the dewatering reagent. Meanwhile, the Fourier-transform infrared (FTIR) spectra of the fresh and spent silica gel suggested that no humins were adsorbed on the silica gel during the fructose-to-EMF/EL conversion (Figure S2), which excluded the possibility of humin adsorption on the dewatering reagent for lowering the recyclability of the catalytic system.…”
Section: Effect Of Water Removal On the Conversion Of Fructose To Emf...mentioning
confidence: 99%